PEMANFAATAN CANVA UNTUK PENINGKATAN KEMAMPUAN GURU PAUD DALAM PENANAMAN NILAI MORAL AGAMA PADA ANAK USIA DINI - Rohita, Rohita; Suwardi; Dody Haryadi (UIN Sunan Kalijaga, 2024)
Instilling religious and moral values in early childhood education is a critical responsibility of educators. Teachers play a central role in presenting concrete and engaging media to help children comprehend these values effectively. However, the utilization of technology as a tool to develop learning media embedded with religious and moral content remains underutilized. This study addresses this gap by enhancing the ability of PAUD teachers to use the Canva application in creating storybooks with religious and moral themes. The activity employed a series of methods, including socialization, training, mentoring, assignments, and continuous support, to equip teachers with the necessary skills. The results demonstrated significant improvements in two key areas: (1) teachers' ability to create storybooks based on religious and moral values, as reflected in titles such as Allah is Most Merciful, Honesty is Cool, Helping Friends, and Rain of God's Grace, and (2) their proficiency in utilizing the Canva application for creative learning media development. This initiative highlights the potential for technology integration in fostering innovative and engaging methods of instilling moral and religious values. It is anticipated that this enhanced capability will contribute to more effective, technology-based pedagogical practices, making value-based learning enjoyable and impactful for children. ================================================= Menanamkan nilai agama dan moral kepada anak didik menjadi tanggungjawab pendidik. Guru memegang peranan penting dalam menghadirkan media konkrit dan menarik untuk membantu anak memahami berbagai materi secara efektif. Masalah yang teridentifikasi adalah rendahnya pemanfaatan teknologi sebagai alat untuk membuat media pembelajaran dengan konten nilai Agama dan moral. Tujuan dilakukannya kegiatan ini adalah untuk meningkatkan kemampuan guru PAUD dalam memanfaatkan aplikasi Canva dan meningkatkan kemampuan guru membuat cerita dengan konten nilai agama moral untuk anak usia dini. Metode yang digunakan adalah sosialisasi, pelatihan, pendampingan, penugasan, dan keberlanjutan. Hasil yang diperoleh menunjukkan adanya peningkatan kemampuan guru PAUD dalam dua (2) indikator yaitu peningkatan kemampuan membuat buku cerita berbasis nilai agama moral terlihat dari karya yang dihasilkan dengan judul: Allah Maha Penyayang; Jujur itu Keren; Menolong Teman; dan Hujan Karunia Allah; dan peningkatan kemampuan memanfaatkan aplikasi Canva yang dimiliki oleh seluruh peserta. Peningkatan kemampuan ini tentu diharapkan akan memberikan dampak pada kemampuan guru menghadirkan pembelajaran berbasis teknologi dalam menanamkan nilai-nilai agama moral dengan cara yang menyenangkan dan inovatif.